1990
DOI: 10.1093/infdis/161.2.185
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Recurrent Herpes Simplex Labialis with Oral Acyclovir

Abstract: In a double-blind, randomized, patient-initiated clinical trial, 174 nonimmunocompromised patients with a history of virus-culture-confirmed herpes simplex labialis were treated with acyclovir capsules, 400 mg five times daily for 5 days, or placebo capsules. For 97% of the patients, treatment started within 1 h of the first sign or symptom of a recurrence. The frequency of positive lesion virus cultures was significantly lower among acyclovir-treated subjects (29/114, 25%) than among placebo-treated subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
58
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(59 citation statements)
references
References 3 publications
0
58
0
1
Order By: Relevance
“…Two studies, one using topical acyclovir cream and one using oral acyclovir, have shown some apparent effect on the prevention of cold sore lesion progression (6,16). However, these results have not been reproduced in subsequent studies (14,19,21). The present valacyclovir studies are the two largest, placebo-controlled trials of herpes labialis treatment designed to test the hypothesis that the progression of cold sore lesions could be prevented with oral medication if taken early (i.e., at the first symptoms).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Two studies, one using topical acyclovir cream and one using oral acyclovir, have shown some apparent effect on the prevention of cold sore lesion progression (6,16). However, these results have not been reproduced in subsequent studies (14,19,21). The present valacyclovir studies are the two largest, placebo-controlled trials of herpes labialis treatment designed to test the hypothesis that the progression of cold sore lesions could be prevented with oral medication if taken early (i.e., at the first symptoms).…”
Section: Discussionmentioning
confidence: 88%
“…This difference as well as other measures of clinical healing was not statistically significant. Spruance et al evaluated a regimen of 400 mg of oral acyclovir 5 times daily for 5 days in comparison with placebo (21). Overall in this study, acyclovir did not affect the duration of the episode, mean maximum lesion size, or the development of lesions, but a subset of early treated patients achieved a 36% mean reduction in pain (P ϭ 0.02) and a 27% mean reduction in time to lesion healing (P ϭ 0.03).…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…This concept received support from two prior clinical trials with peroral ACV and topical idoxuridine in dimethyl sulfoxide which showed that antiviral nucleoside efficacy was limited to the patients who initiated treatment in the prodrome or erythema lesion stage (18,19). One potential explanation for the discrepancy between the peroral ACV and topical idoxuridine in dimethyl sulfoxide studies on the one hand and the penciclovir and ACV cream trials on the other is that the delivery of drug to the site of virus replication was far more efficient by the oral route of administration and from the dimethyl sulfoxide vehicle than from the cream vehicles (14).…”
Section: Discussionmentioning
confidence: 99%
“…ACV (5%) ointment (Zovirax ointment) accelerated healing of herpes labialis in immunocompromised patients (22). Peroral administration of 400 mg of ACV five times/day for 5 days significantly reduced virus shedding and reduced lesion healing time and the duration of lesion pain among the subgroup of patients who started treatment "early" (in the prodrome or erythema lesion stage) (19). Peroral ACV administered as prophylaxis at 400 mg two times/day significantly reduces the frequency of recurrent episodes and prevents herpes-associated erythema multiforme (4,8,11).…”
mentioning
confidence: 99%